ASSESSMENT AND COMPENSATION OF HEALTH, LIFE AND EMOTIONAL DAMAGES RESULTING FROM CRIMINAL ACTS IN MONGOLIA - Otgonsuren Chuluun, (International Journal of Innovative Technologies in Social Science, 2025)
This study explores the existing legal framework for assessing compensation for human life, health, and emotional harm, highlighting key obstacles and proposing recommendations for enhancing compliance with global norms.Changes in the political, socio-economic, and economic aspects of any country are ultimately reflected in laws and other legal acts. Law serves as the driving force of society. However, the control and management of this driving force depend on the individual, who is an integral part of society. Therefore, the essence of a state governed by the rule of law largely hinges on the guarantee and protection of human rights and freedoms.According to international norms, Article 2.27 of the Universal Declaration of Human Rights stipulates that “Everyone has the right to compensation for material and psychological damage.” Similarly, Article 16, Part 1 of the Mongolian Constitution asserts that “everyone has the right to life,” and Article 14 grants individuals the right to seek protection of their rights through the court system if they believe their rights have been violated. Personal life, health, honor, and reputation are recognized and safeguarded as fundamental human rights and freedoms.Therefore, it is essential to comprehensively address non-economic harm to human life, health, and mental well-being, as well as issues such as defamation and slander, and the legal mechanisms for their resolution and compensation.